ANALYSIS OF “CLASSICAL” AND LEGISLATIVE DEFINITIONS FOR THE TERM RECORDS OF THE SLOVAK TERMINOLOGY DATABASE - LEVICKÁ, Jana (Comparative Legilinguistics, 2009)
The paper presents a comparative study of "classical" and legislative definitions referring to the same concept in the field of law, which reveal multidimensional nature of these concepts. The author focuses on one hand on typology of definitions and on the other on their structure, coherence and applicability. The aim is to decide, on the basis of this comparison, which type of definition is to be used to represent concepts in the domain of law in the Slovak Terminology Database, addressing not only lawyers but also lay public, so that definitions included in this Database can facilitate and enhance knowledge acquisition.